2020
DOI: 10.1101/2020.11.27.401430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural excitability and sensory input determine intensity perception with opposing directions in initial cortical responses

Abstract: Perception of sensory information is determined by stimulus features (e.g., intensity) and instantaneous neural states (e.g., excitability). Commonly, it is assumed that both are reflected similarly in evoked brain potentials, that is, higher evoked activity leads to a stronger percept of a stimulus. We tested this assumption in a somatosensory discrimination task in humans, simultaneously assessing (i) single-trial excitatory post-synaptic currents inferred from short-latency somatosensory evoked potentials (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 61 publications
4
14
0
Order By: Relevance
“…Moment-to-moment fluctuations of neural responses to sensory stimuli play a critical role in how we perceive the external world. Commonly, it is assumed that instantaneous neural states influence the stimulus-related brain responses, which in turn shape the perceptual outcome (e.g., Arieli et al, 1996; McCormick et al, 2020; Sadaghiani et al, 2010; Stephani et al, 2021). Specifically, this may be achieved through the modulation of cortical excitability, which is assumed to shift the sensory threshold of stimulus perception (Samaha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moment-to-moment fluctuations of neural responses to sensory stimuli play a critical role in how we perceive the external world. Commonly, it is assumed that instantaneous neural states influence the stimulus-related brain responses, which in turn shape the perceptual outcome (e.g., Arieli et al, 1996; McCormick et al, 2020; Sadaghiani et al, 2010; Stephani et al, 2021). Specifically, this may be achieved through the modulation of cortical excitability, which is assumed to shift the sensory threshold of stimulus perception (Samaha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this may be achieved through the modulation of cortical excitability, which is assumed to shift the sensory threshold of stimulus perception (Samaha et al, 2020). Using electroencephalography (EEG) or magneto-encephalography (MEG), this phenomenon can be observed in various sensory modalities in humans, such as the visual (Busch et al, 2009; Iemi et al, 2017), auditory (Henry et al, 2016; Müller et al, 2013), and somatosensory domain (Baumgarten et al, 2016; Craddock et al, 2017; Forschack et al, 2020; Stephani et al, 2021), where instantaneous neural states have typically been quantified by prestimulus oscillatory activity in the alpha frequency range (8-13 Hz), a common marker of the excitability state of a given cortical brain region (Jensen and Mazaheri, 2010; Klimesch et al, 2007; Romei et al, 2008). Noteworthy, in the somatosensory domain, also activity in the beta frequency range (15–30 Hz) may have a similar modulatory effect on sensory processing (Anderson and Ding, 2011; Jones et al, 2010; van Ede et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the visuospatial perception task by Perl et al (2019), decreased alpha power has been observed in postcentral and parahippocampal gyrus during inspiration compared to expiration. Analogously, lower pre-stimulus alpha power in central brain areas (Mu rhythm) has been associated with higher neural excitability reflected in improved conscious tactile perception (Schubert et al, 2009; Nierhaus et al, 2015; Craddock et al, 2017; Forschack et al, 2020; Stephani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the course of alpha power – known to be inversely related to excitability – across the respiratory cycle has been shown to have a minimum around expiration onset (Kluger et al, 2021) – the time period when in our study most stimuli were timed. Also for tactile stimuli, it has been shown that alpha power in central brain areas is related to conscious detection (Schubert et al, 2009; Nierhaus et al, 2015; Craddock et al, 2017; Forschack et al, 2020; Stephani et al, 2021). Taken together, respiration phase locking might be used to increase the likelihood to detect faint stimuli in a phase of highest cortical excitability (attention).…”
Section: Discussionmentioning
confidence: 99%